ANTI-RACISM DISCOURSE IN TOI MOI SONG - Leni Tiwiyanti; Yuli Sofiani Zaimar; Yosi M Passandaran (Journal of English Language Teaching and Literature (JELTL), 2023)
Songs are typically composed for certain goals, messages, and audiences, and occasionally they are produced with particular listeners in mind. Common subjects in song lyrics include societal and current issues and challenges, with which the artist tries to communicate through manifestations of his or her beliefs, feelings, and ideologies. Therefore, language research to song lyrics is indeed very interesting to do, because it examines meaning. This research is interested in researching a song lyric entitled Toi Moi by Kids United. The researchers are interested in examining the anti-racism contained in it. The method in this research is qualitative and descriptive. This research uses van Dijk's critical discourse analysis theory, with elements of macro structure, super structure and micro structure. After that, the researchers would like to see the representation in this song. After deeper analysis, researchers found different meanings The result of the research is that not everything that is stated in a text will be the same as what is implied. Indeed, when we analyze macro structure, we interpreted, this song talks about a unity about two person or lovers. However, after researching deeper, by analyzing superstructure and micro structure the researchers found that the deeper meaning behind this song lyric is about racism and not about love story between two lovers. So, discourse analysis can be applied to analyze the deep meaning in a text.